Vpliv spola na parametre telesne dejavnosti in sladkorne bolezni pri sladkornih bolnikih tipa 1 - Zdolšek, Anže (Šport (Ljubljana), 2019)
In our research we examined gender differences of different types of physical activity, diabetes mellitus parameters, blood pressure and lipids in individuals with type 1 diabetes (T1D). We divided physical activity into vigorous physical activity, moderate physical activity and non-exercise activity thermogenesis (NEAT). NEAT is energy expanded for everything we do that is not sleeping, eating or sportslike exercise (household chores, mowing, energy expanded with transport ...). In our research participated 109 (55 women, 54 men) T1D patients with average age of 38 +- 10 years, weight 77,33 +- 15,70 kg and HbA1c 7,03 +- 0,89 %. Patients completed questionnaire about physical activity, NEAT and frequency of hypoglycaemia. We also noted basic parameters of therapy (insulin dose, blood pressure, cholesterol, HbA1c). Men patients had higher bolus and overall insulin dosage compared to women. We also found statistical difference in vigorous physical activity and NEAT. Men patients had higher rate of vigorous physical activity while women patient had higher NEAT score. Women patients also had lower value of systolic blood pressure, diastolic blood pressure and higher value of HDL cholesterol.
Keywords: diabetes; gender differences; nevadbena termogeneza; non-exercise activity thermogenesis; physical activity; razlike; sladkorna bolezen tip 1; spol; sport; šport; telesna dejavnost; type 1